Ответ(ы) на вопрос:
1.
[latex]\frac{2x}{x^2-4y^2}+\frac{1}{x+2y}-\frac{1}{2y-x}=\frac{2x}{(x-2y)(x+2y)}+\frac{1(x-2y)}{(x+2y)(x-2y)}-\frac{1}{-(-2y+x)}=\\\\\frac{2x+x-2y}{(x-2y)(x+2y)}+\frac{1(x+2y)}{(x-2y)(x+2y)}=\frac{3x-2y+x+2y}{(x-2y)(x+2y)}=\frac{4x}{x^2-4y^2}[/latex]
2.
[latex]\frac{x}{x^2-y^2}-\frac{x}{(x-y)^2}*\frac{(y-x)^2}{2x}-\frac{x}{x+y}=\\\frac{x}{(x-y)(x+y)}-\frac{x(x-y)}{(x+y)(x-y)}-\frac{1}{(x-y)(x-y)}*\frac{(y-x)(y-x)}{2}=\\\frac{x-x^2+xy}{(x-y)(x+y)}-\frac{1}{-1(-x+y)(x-y)}*\frac{(y-x)(y-x)}{2}=\\\frac{x-x^2+xy}{(x-y)(x+y)}-\frac{1}{-1(x-y)}*\frac{y-x}{2}=\frac{x-x^2+xy}{(x-y)(x+y)}-\frac{1}{-x+y}*\frac{y-x}{2}=\\\frac{x-x^2+xy}{(x-y)(x+y)}-\frac{1}{2}=\frac{2(x-x^2+xy)}{2(x-y)(x+y)}-\frac{1(x-y)(x+y)}{2(x-y)(x+y)}=\frac{2x-2x^2+2xy-x^2+y^2}{2(x^2-y^2)}=\\\\[/latex][latex]\frac{2x-3x^2+2xy+y^2}{2x^2-2y^2}[/latex]
Не нашли ответ?
Похожие вопросы